Integrating Task-Based Instruction with Other Teaching Approaches (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
This study explores the integration of Task-Based Instruction (TBI) with other teaching approaches to enhance language learning outcomes. TBI, known for its focus on real-world tasks and communicative competence, is examined in conjunction with traditional grammar-focused instruction, content-based instruction (CBI), and project-based learning (PBL). The research investigates how these combined methods influence the development of language skills, learner motivation, and overall classroom dynamics. Results indicate that an integrated approach can offer a balanced development of fluency and accuracy, while also catering to diverse learner needs.